Prehospital Tibial Intraosseous Drug Administration is Associated with Reduced Survival Following Out of Hospital Cardiac Arrest: A study for the CARES Surveillance Group. (October 2021) - Hamam, Mohamed Serhan; Klausner, Howard A.; France, John; Tang, Amy; Swor, Robert A.; Paxton, James H.; O'Neil, Brian J.; Brent, Christine; Neumar, Robert W.; Dunne, Robert B.; Reddi, Swetha; Miller, Joseph B.
Abstract: Background: Recent reports have questioned the efficacy of intraosseous (IO) drug administration for out-of-hospital cardiac arrest (OHCA) resuscitation. Our aim was to determine whether prehospital administration of resuscitative medications via the IO route was associated with lower rates of return of spontaneous circulation (ROSC) and survival to hospital discharge than peripheral intravenous (IV) infusion in the setting of OHCA. Methods: We obtained data on all OHCA patients receiving prehospital IV or IO drug administration from the three most populous counties in Michigan over three years. Data was from the Michigan Cardiac Arrest Registry to Enhance Survival (CARES) database. The association between route of drug administration and outcomes was tested using a matched propensity score analysis. Results: From a total of 10, 626 OHCA patients, 6869 received parenteral drugs during their prehospital resuscitation (37.8% by IO) and were included in analysis. Unadjusted outcomes were lower in patients with IO vs. IV access: 18.3% vs. 23.8% for ROSC (p < 0.001), 3.2% vs. 7.6% for survival to hospital discharge (p < 0.001), and 2.0% vs. 5.8% for favorable neurological function (p < 0.001). After adjustment, IO route remained associated with lower odds of sustained ROSC (OR 0.72, 95% CI 0.63–0.81, p < 0.001), hospital survival (OR 0.48, 95% CI 0.37–0.62, p < 0.001), and favorable neurological outcomes (OR 0.42, 95% CI 0.30–0.57, p < 0.001). Conclusion: In this cohort of OHCA patients, the use of prehospital IO drug administration was associated with unfavorable clinical outcomes.